Structure, tautomerism, spectroscopic and DFT study of o-vanillin derived Schiff bases containing thiophene ring - Rodríguez, María Rosa (2018)
Two Schiff bases derived from o-vanillin (o-HVA), a well-known antioxidant hydroxo aldehyde, have been obtained from condensation with 2-thiophenecarboxilic acid hydrazide (TPNNH) and 2-thiophenemethylamine (TPNH2), respectively. The inclusion of thiophene is based on its significance in the development of effective therapeutic agents. The study of the compounds oVATPNNH and oVATPNH2 includes solid state structural and spectroscopic analysis by single-crystal X-ray diffraction and vibrational spectroscopy (FTIR and Raman). The crystal structure of oVATPNH2 shows a peculiar rotational disorder in the heterocycle. Tautomeric equilibria in solution, which depends on the molecule structure and the nature of the solvent, were analysed by means of 1H and 13C{1H} NMR along with electronic spectroscopy. Tautomerism plays an important role not only in the molecular interactions but also in the behaviour of the Schiff base when acting as a ligand in coordination compounds. Results obtained from DFT calculations were used in the interpretation of the experimental data and in the spectral assignments.